Através do espelho: o PL 6.998/2013 à luz do gênero - Tardelli, Priscila Rodrigues Naves (2021)
Gender and childhood are rarely placed under the same perspective, making the panoramas of childhood in gender and gender studies in childhood studies unusual. In the second group, the adultcentric view still prevails, with the perspective focused on the research expectations of adults in the social constructions that permeate childhood. Through bibliographical research, it was established, as a starting point, that patriarchal domination also affects children in the logic of power relations, remaining in a lower position than adults, as well as women in relation to men. In order to recognize the importance and specificities of Early Childhood, in 2013, Bill No. 6.998 was proposed to discuss the guidelines for the elaboration of public policies aimed at this public. In the analysis of the discussions, amendments and propositions of this Project, attention was focused on the relevance of gender issues in the discussions raised; whether the gender category would be considered as a factor in the elaboration of public policies for Early Childhood. Next, we analyzed the advances in girls' rights in Brazil, from the perspective of the Sustainable Development Goals (SDGs), elaborated by the United Nations in 2015 – also known as the 2030 Agenda. Thus, it was possible to unveil the advances from the gender perspective in the guidelines for Early Childhood and the Brazilian position in the fulfillment of the 2030 Agenda, in search of a more accessible and egalitarian society.